A new complex of silver(I) with probenecid: Synthesis, characterization, and studies of antibacterial and extended spectrum β-lactamases (ESBL) inhibition activities - Lustri, Wilton R.; Lazarini, Silmara C.; Simei Aquaroni, Nayara Ap.; Resende, Flávia A.; Aleixo, Nadia A.; Pereira, Douglas H.; Lustri, Bruna Cardinali [UNESP]; Moreira, Cristiano Gallina [UNESP]; Ribeiro, Camila M. [UNESP]; Pavan, Fernando R. [UNESP]; Nakahata, Douglas H.; Gonçalves, Adriano M. [UNESP]; et al. (Elsevier, 2023)
This article describes the in vitro antibacterial and β-lactamase inhibition of a novel silver(I) complex with the sulfonamide probenecid (Ag-PROB). The formula Ag2C26H36N2O8S2·2H2O for the Ag-PROB complex was proposed based on elemental analysis. High-resolution mass spectrometric studies revealed the existence of the complex in its dimeric form. Infrared, nuclear magnetic resonance spectroscopies and Density Functional Theory calculations indicated a bidentate coordination of probenecid to the silver ions by the oxygen atoms of the carboxylate. In vitro antibacterial activities of Ag-PROB showed significant growth inhibitory activity over Mycobacterium tuberculosis, S. aureus, and P. aeruginosa PA01biofilm-producers, B. cereus, and E. coli. The Ag-PROB complex was active over multi-drug resistant of uropathogenic E. coli extended spectrum β-lactamases (ESBL) producing (EC958 and BR43), enterohemorrhagic E. coli (O157:H7) and enteroaggregative E. coli (O104:H4). Ag-PROB was able to inhibit CTX-M-15 and TEM-1B ESBL classes, at concentrations below the minimum inhibitory concentration for Ag-PROB, in the presence of ampicillin (AMP) concentration in which EC958 and BR43 bacteria were resistant in the absence of Ag-PROB. These results indicate that, in addition to ESBL inhibition, there is a synergistic antibacterial effect between AMP and the Ag-PROB. Molecular docking results revealed potential key residues involved in interactions between Ag-PROB, CTX-M-15 and TEM[sbnd]1B, suggesting the molecular mechanism of the ESBL inhibition. The obtained results added to the absence of mutagenic activity and low cytotoxic activity over non-tumor cell of the Ag-PROB complex open a new perspective for future in vivo tests demonstrating its potential of use as an antibacterial agent.
Keywords: Antibacterial agent; Molecular docking; Multi-drug resistant; Probenecid; Silver complex; β-lactamase inhibition